Eukaryotic Cell Biomimetics: Construction of Eukaryotic Cell Biomimetics: Hierarchical Polymersomes‐in‐Proteinosome Multicompartment with Enzymatic Reactions Modulated Protein Transportation (Small 7/2021). Issue 7 (18th February 2021) - Wen, Ping; Wang, Xueyi; Moreno, Silvia; Boye, Susanne; Voigt, Dagmar; Voit, Brigitte; Huang, Xin; Appelhans, Dietmar
Abstract : Different membrane characteristics regulate biological pathways in eukaryotic cells. In article number 2005749, Xin Huang, Dietmar Appelhans, and co‐workers demonstrate the function of orthogonal‐responsive membranes of eukaryotic cell biomimetics for the modulation of protein transport.